2020
DOI: 10.1002/wrna.1617
|View full text |Cite
|
Sign up to set email alerts
|

The multifaceted role of PARP1 in RNA biogenesis

Abstract: Poly(ADP‐ribose) polymerases (PARPs) are abundant nuclear proteins that synthesize ADP ribose polymers (pADPr) and catalyze the addition of (p)ADPr to target biomolecules. PARP1, the most abundant and well‐studied PARP, is a multifunctional enzyme that participates in numerous critical cellular processes. A considerable amount of PARP research has focused on PARP1's role in DNA damage. However, an increasing body of evidence outlines more routine roles for PARP and PARylation in nearly every step of RNA biogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 172 publications
(264 reference statements)
1
26
0
Order By: Relevance
“…A follow up study found that RNAPII elongation rate was also modulated at these sites depending on chromatin structure, which is disrupted upon PARP1 depletion ( 67 ). PARP1, in addition to its role as a PARylation activator, has been linked to regulation of transcription and AS via multiple mechanisms involving chromatin modulation, transcriptional modulation, post-transcriptional regulation of RNA-binding proteins and mRNA stabilization (reviewed in ( 68 , 69 )). While this is true, possible roles for CTCF in the regulation of AS via activating PARP1 and PARylation will reveal new aspects of AS regulatory mechanisms, which require further investigation (Figure 2B ).…”
Section: Co-transcriptional Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…A follow up study found that RNAPII elongation rate was also modulated at these sites depending on chromatin structure, which is disrupted upon PARP1 depletion ( 67 ). PARP1, in addition to its role as a PARylation activator, has been linked to regulation of transcription and AS via multiple mechanisms involving chromatin modulation, transcriptional modulation, post-transcriptional regulation of RNA-binding proteins and mRNA stabilization (reviewed in ( 68 , 69 )). While this is true, possible roles for CTCF in the regulation of AS via activating PARP1 and PARylation will reveal new aspects of AS regulatory mechanisms, which require further investigation (Figure 2B ).…”
Section: Co-transcriptional Regulationmentioning
confidence: 99%
“…Given its direct effect on PARP1 and its PARylation activity ( 60 , 61 ), CTCF might possibly regulate AS via RNA-binding proteins, whose binding, recruitment and expression are directly regulated by PARP1 and/or PARylation ( 68 ) (Figure 2B and C ). This could be tested by examining the effect of CTCF on PARP1-mediated recruitment of SF3B1 and subsequently pre-mRNA splicing ( 66 ).…”
Section: Co-transcriptional Regulationmentioning
confidence: 99%
“…In the context of global BER/SSBR, CRISPR-mediated KO of PARP1 is shown to prevent the formation of BER/SSBR protein complexes at sites of laser-induced DNA damage [366]. Recent studies have also suggested a complicated role for PARP1 in RNA biology, a role for RNA in PARP1 activation, and possibly as a target of PARP1 activation [367][368][369][370][371][372][373]. Further, Krauss et al suggest the snoRNAs may be endogenous PARP1 activators, confirmed by creating CRISPR/Cas9-mediated KO of snoRNAs in cells [374].…”
Section: Ber/ssbr Lesion Recognition and Strand Scissionmentioning
confidence: 99%
“…Poly(ADP-ribose) polymerase 1 (PARP-1) is one of the most abundant nuclear protein. PARP-1 is a multifunctional enzyme acting at numerous levels to regulate transcription [93]. Interestingly, Yoo et al identified that PARP-1 is necessary for LPS-induced, but not IFNγ-induced Cas-11 expression.…”
Section: Caspase-11mentioning
confidence: 99%